Noninvasive assessment of liver fibrosis in chronic hepatitis B carriers with sound touch elastography: study of surgical pathology specimens. (2nd August 2020) - Yang, Lulu; Li, Jiawu; Ma, Lin; Xiang, Hongjin; He, Du; Lu, Changli; Tang, Lin; Luo, Yan; Chen, Shigao
ABSTRACT: Purpose: To evaluate the diagnostic performance of sound touch elastography (STE) for staging liver fibrosis in chronic hepatitis B (CHB) patients using pathological stage of surgical specimens as the reference standard. Method: 239 CHB patients were included. Liver stiffness measurements (LSMs) on STE and Supersonic shear imaging (SSI), gamma glutamyl transferase-to-platelet ratio (GPR), aspartate aminotransferase-to-platelet ratio index (APRI) and four-factor Fibrosis-4 (FIB-4) index were obtained. Areas under the receiver operating characteristic (ROC) curves (AUCs) for the diagnosis of fibrosis stage were calculated and compared. Results: The LSMs obtained by STE and SSI significantly correlated with the fibrosis stages (r = 0.757; r = 0.758, respectively, both p < 0.001). No significant differences in AUCs were observed between STE and SSI in identifying fibrosis ≥stage 1 (0.92 vs. 0.94), ≥stage 2 (0.89 vs. 0.91), ≥stage 3 (0.90 vs. 0.91) or stage 4 (0.92 vs. 0.91). Both STE and SSI had significantly higher AUCs in identifying each fibrosis stage than the GPR (0.68, 0.77, 0.76 and 0.79), APRI (0.53, 0.66, 0.74 and 0.69) and FIB-4 (0.61, 0.77, 0.79 and 0.74). Conclusions: STE is an efficient tool for assessing liver fibrosis in CHB patients, with performance comparable to that of SSI and superior to that of biomarkers.